Development of new laws in the management of stratified properties: a Malaysian experience - Mohamad, Nor Asiah (2007)
Malaysia has recently announced a few amendments to the present laws governing the stratified properties including the introduction of new law to manage and maintain the properties. The objectives of the amendments among other things are to provide a better delivery system in the public sector as well as to have an orderly housing laws and efficient management of high-rise building in Malaysia. The much awaited laws, though well welcome, create considerable doubts and worries in its implementation as regards to the commitment that may be given by all relevant parties in managing the special type of properties. This paper seeks to highlight some of the lingering doubts shadowing the implementation of the laws and policies and it is submitted that those areas require reasonable and due cognizance from all, in particular, the major key-players dealing with the matter. It is argued that the effectiveness and the success of the implementation will highly depend on the commitment of all involved in the industry. The law gives more power to property owners to self regulate the management of the properties which at the same time call for a serious and highest commitment from the property owners. The future demands in management of high-rise building does not require for financial contribution from all owners, but at the same time it compels for a serious commitment towards a collective management from all strata owners.